2015
DOI: 10.1179/1743290114y.0000000118
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of SiC particles reinforced Mg–8Al–1Sn magnesium matrix composites fabricated by powder metallurgy

Abstract: The new type of Mg-8Al-1Sn (AT81) magnesium matrix composites reinforced with different volume fractions (5, 10, 15, 20, 25 and 30 vol.-%) of SiC particles (average size of 10 mm) was fabricated by powder metallurgy. With the increasing volume fraction of SiC particles (SiC p ), the particles gradually show more homogeneous distribution. Compared with the AT81 alloy, the yield strength (YS) and ultimate compressive strength of the SiC p /AT81 composites are improved simultaneously. With the increasing SiC p fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The resultant lower failure strain in the Mg-5CCA composite can be accounted for with the influence of small grains from the grain distribution measurement (Figure 4c) and microstructural observation (Figure 5c). [17] 89 ± 3 368 ± 8 15.1 ± 1.5 Mg-5 vol % Ni 60 Nb 40 [18] 130 ± 11 320 ± 11 18.4 ± 1.3 AT81-5 vol % SiC [9] 127 ± 10 301 ± 20 11.4 ± 0.5 AZ91D-3 vol % TiC [10] -320 failure strain to Mg and its composites (Table 2). However, the average failure strain in Mg-5CCA was found to be lower than that in Mg-2.5CCA and Mg-7.5CCA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant lower failure strain in the Mg-5CCA composite can be accounted for with the influence of small grains from the grain distribution measurement (Figure 4c) and microstructural observation (Figure 5c). [17] 89 ± 3 368 ± 8 15.1 ± 1.5 Mg-5 vol % Ni 60 Nb 40 [18] 130 ± 11 320 ± 11 18.4 ± 1.3 AT81-5 vol % SiC [9] 127 ± 10 301 ± 20 11.4 ± 0.5 AZ91D-3 vol % TiC [10] -320 failure strain to Mg and its composites (Table 2). However, the average failure strain in Mg-5CCA was found to be lower than that in Mg-2.5CCA and Mg-7.5CCA.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The resultant lower failure strain in the Mg-5CCA composite can be accounted for with the influence of small grains from the grain distribution measurement (Figure 4c) and microstructural observation (Figure 5c). [17] 89 ± 3 368 ± 8 15.1 ± 1.5 Mg-5 vol % Ni60Nb40 [18] 130 ± 11 320 ± 11 18.4 ± 1.3 AT81-5 vol % SiC [9] 127 ± 10 301 ± 20 11.4 ± 0.5 AZ91D-3 vol % TiC [10] -320 * 17 * * Values approximated from the Compression graph. When compared to Mg composites containing ball-milled amorphous particles with a comparable amount of reinforcement addition, a significant improvement in compressive yield strength and ultimate compressive strength was observed in the Mg composite containing CCA particles while maintaining a similar compressive failure strain level (Table 2).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Guleryuz et al 25 26 reported that the addition of 'SiC and Mg' increases the microhardness, CoF, density, wear resistance, less porosity, good bond formation and also enhances the embrittling effect to hybrid MMCs. Luo et al 27 evaluated the effects of volume percentage of SiC on Mg-8Al-1Sn through powder metallurgy. The compression strength of the samples has increased with the increase in volume of the reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…The metal matrix's reinforcing materials can be ceramic particles or fibers that offer high mechanical strength and high modulus of elasticity, properties that make them optimal materials in various technological applications [9]. The most commonly reinforcement materials are, SiO 2 [10], Al 2 O 3 [11], Y 2 O 3 [12], ZrO 2 [13], TiC [14], B 4 C [15], SiC [16], Si 3 N 4 [17], graphene [18], fullerenes [19], and carbon nanotubes (CNTs) [20].…”
Section: Introductionmentioning
confidence: 99%